Clothing purchase habits and how it affects the willingness to buy convertible clothing a study on selected women working in Makati City - Encabo, Hazel P.
ABSTRACT The study focused on the current clothing purchase habits of selected women working in Makati City. Specifically, it determined how such habits affect their willingness to buy convertible clothing, Factors which are considered important when it comes to a working woman's garment spending and what aspects of her life influence those choices were also analyzed.